The use of vitamin D in depression - Klaus W. Lange; Katharina M. Lange; Yukiko Nakamura; Andreas Reissmann (Journal of Food Bioactives, 2021)
Vitamin D has increasingly been associated with the pathophysiology of mental illness and has been suggested to have beneficial effects on depression in adults. Epidemiological studies concerning vitamin D and depression have found inconsistent results and many have significant methodological limitations. The available evidence suggests that depressed individuals show reduced vitamin D concentrations compared to controls without depression. Despite the available findings suggesting that hypovitaminosis D elevates the risk of depressive mood, the evidence of observational and interventional studies is insufficient to establish causality between low vitamin D levels and the occurrence of depression. The question of whether vitamin D sufficiency has protective efficacy against incident depression or recurrence requires future investigation. In order to examine the therapeutic efficacy of vitamin D, further well-designed, large-scale, long-term intervention trials of vitamin D supplementation in people of different age groups with depressive symptoms, diagnosed depression, postpartum depression or other depressive disorders are warranted. In short, current evidence cannot definitively establish whether vitamin D deficiency is a risk factor in the development of depression or whether vitamin D is effective in the treatment of depression.